Pengaruh Kompleksitas Operasi Solvabilitas dan Auditor Switching Terhadap Audit Delay Perusahaan Pertambangan - Yonia Bangnga Pasande; Rina Hartanti (Peneliti.net, 2023)
The purpose of this research is to analyze the effect of Operational Complexity, Solvability, and Auditor Switching on Audit Delay. The data used is secondary data obtained from the Indonesia Stock Exchange. The research population is Mining Sector Companies during 2017-2021. The sampling technique uses a purposive sampling approach with a total of 125 samples. This study uses the Multiple Linear Regression model. The results of hypothesis testing conducted in this study indicate that Operational Complexity and Solvability has a positive effect on Audit delay,, Auditor Switching has a negative effect on Audit delay.